THE EFFECT OF APPLYING TALKING CHIPS TECHNIQUE ON THE STUDENTS’ ACHIEVEMENT IN SPEAKING ABILITY - Maridha Fitri; Wina Viqa Sari; Eliyati Eliyati; Nurul Aisyah (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
The objective of this research was 1) to find out the effect of applying talking chips on students’ achievement in speaking 2) to find out the students’ difficulties of applying talking chips technique in learning speaking. The experimental research method was applied in this study. The population was the 2013/2014 first grade of SMA HARAPAN MEKAR jalan Marelan No. 77 Medan which consisted of 60 students. All of the population was taken as the sample. The students were divided into two groups, namely experimental and control group. The experimental group was taught by talking chips while control group was taught by discussion method. The instrument was used in this study was essay test. The essay test consisted of 5 items; the test was teacher-made test. The data was analyzed by using t-test formula. The findings showed t-observed= 2.45, while t-table=2.02. Based on the findings above, t-observed bigger than t-table (2.45>2.02). It means that the students who were taught by applying talking chips were better than those who were taught by discussion method. So, it can be said that alternative hypothesis (Ha) was accepted.